DIPLOMASI INDONESIA DAN KOREA SELATAN DI BIDANG KERJASAMA PERTAHANAN TAHUN 2008-2014 - Muthia Zulkarnain; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research describe the diplomacy of Indonesia with South Korea in defence and security. Asia Pacisif are one of region in the world that have strategic potency espcecially about the interest of the superpower states likes United State of America and China. In order that to increase a power in defence scope, so Indonesia have make a agreement with South Korea to create some cooperations for the another states.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the diplomacy of Indonesia with South Korea in defence and security. The theories applied in this research are realism with the nations state analyze, national interest concept and the diplomacy setting theory.The research shows that the diplomacy of Indonesia with South Korea in defence and security are have done by create a confidence building measures. The implementations of this policy are have done by cooperations in military and defence between Indonesia and South Korea. The cooperations between Indonesia and South Korea area have done because the domestic and internationals threat.Key words: diplomacy, agreements, military and defence.